Synthesis of bifunctional nanocatalyst from waste palm kernel shell and its application for biodiesel production. Issue 45 (21st July 2020) - Abdullah, Rose Fadzilah; Rashid, Umer; Taufiq-Yap, Yun Hin; Ibrahim, Mohd Lokman; Ngamcharussrivichai, Chawalit; Azam, Muhammad
Abstract : The potential of bifunctional nanocatalysts obtained from waste palm kernel shell (PKS) was investigated for one-step transesterification–esterification under mild conditions. Abstract : The potential of bifunctional nanocatalysts obtained from waste palm kernel shell (PKS) was investigated for one-step transesterification–esterification under mild conditions. State-of-the-art characterization illustrated that the synthesized catalyst has high stability through the thermal test, high BET surface area of 438.08 m 2 g −1, pore volume of 0.367 cm 3 g −1 and pore width of 3.8 nm. The high amount of basicity (8.866 mmol g −1 ) and acidity (27.016 mmol g −1 ) promoted the successfulness of simultaneous transesterification–esterification. The investigation revealed that the combination of potassium and copper on activated carbon surface showed good catalytic activity by giving 95.0% FAME yield and 97.3% FFA conversion at a relatively mild condition of 5 wt% catalyst loading, 12 : 1 methanol to oil molar ratio at 80 °C for 4 hours with FAME yield > 80% after 5 reaction cycles. Characterization of the spent catalyst showed that the amount of basicity was reduced to 3.106 mmol g −1, which validated the reduction of the catalytic performance. The usage of waste material was successfully discovered in producing an effective bifunctional catalyst for biodiesel production from waste cooking oil (WCO) and has high potential for commercialization in the future.